Social Counciousness in Khalid Fateh Muhammad’s Novel “Zina” - Sadia Imtiaz Dr. Mushtaq Adil (دریافت)
Khalid Fateh Mohammad is one of the most famous novelists of the 21st century. His work is an interesting school of diverse themes, however, mainly about recurring mundane issues that concern common people. These include love/hate relationship, life struggles and social/psychological problems which essentially result from the vicious corollary of existing social inequalities in our society. Khalid Fateh Muhammad’s relatively recent novel زینہ is varied in its subject matter. In it, he unpicks social evils including sectarianism, terrorism, yellow journalism and black magic, to name a few, and brings forth what follows at their heels, underlining their ramifications for our societal fabric. The novel also highlights how some people are fated to struggle all their life in vain whereas for others nature itself paves the way to success and prosperity.  In this article, we have primarily analyzed the contribution of Khalid’s novel زینہ in creating a particular kind of social consciousness in our society.